Estudio de un dique ubicado junto al margen derecho del Río Bapao cantón Daule - Galarza Palma, Miguel Ángel (2013)
The rivers and canals in winter season are usually a big problem for the residents who live near them because any country has escaped the dangers and disasters that can cause these great avenues. Knowing the causes or how commonly such avenues behave is essential in order to avoid those disasters. Protections, made of soil, stone, concrete or any other mini or superstructure require hydrologic and hydraulic data to proceed to the design of such structures….......